CONSTRAINING SPACETIME TORSION WITH THE MOON, MERCURY AND LAGEOS - March, Riccardo; Bellettini, Giovanni; Tauraso, Roberto; Dell’Agnello, Simone (Acta Polytechnica, 2013)
We consider an extension of Einstein General Relativity where, beside the Riemann curvature tensor, we suppose the presence of a torsion tensor. Using a parametrized theory based on symmetry arguments, we report on some results concerning the constraints that can be put on torsion parameters by studying the orbits of a test body in the solar system.